Optimization of CO2 laser power for patterning of single-layer graphene for advanced devices applications - Kumar, P. (Institute of Electrical and Electronics Engineers Inc., 2019)
Transparent conductive films (TCFs) made of graphene and its composite materials have emerged as potential electrodes for advanced devices such as sensors, light emitting diodes (LEDs), organic LEDs, solar cells and supercapacitors. The TCFs need to be patterned to make their use in these devices. In this work, the patterning of such TCF is carried out by CO2 laser. Different laser power levels are optimized for effective patterning of single-layer graphene film transferred to the transparent substrates such as microscopic glass slides and polyethylene terephthalate (PET). Moreover, the effect of different laser power levels on the electrical property of graphene TCFs before and after patterning is also examined. It is found that the patterned graphene TCFs are free from film narrowing, wrapping, and bundle formation at different power levels. It is also found that the sheet resistance of patterned graphene film remains the same after CO2 laser-based ablation process. The optimized conditions of CO2 laser-based patterning offer a facile, fast, and time-saving technique to pattern the single layer graphene. Â© 2019 IEEE.